The Mapping of Vocational Competencies Based on Regional Potential Using Geographic Information System - Meirawan, Danny; A, Ana; Eko Lusiana, Awindha; Aryanti, Tutin (International Journal of Engineering and Technology, 2018)
Regional potential based approach is one of the strategies to create quality human resources that can develop regional potential. Vocational competence which is not in line with the local potential has become a problem in one of regencies in Indonesia namely Tangerang Regency. The purpose of this study was to map vocational competencies in Tangerang Regency based on the potential using the Geographic Information System (GIS). GIS is used to help school mapping so that educational planning can be well realized. This research uses a qualitative approach with descriptive research methods. The data analysis uses LQ and PCA analysis. The results of the LQ analysis show that there are 10 districts that have industrial potential, 14 districts with livestock potential, 4 districts with fishery potential and 19 districts with agricultural potential. The results of the PCA analysis show that there are 14 districts which become priority locations for vocational school development. The mapping of vocational competencies which is based on regional potential in Tangerang Regency uses GIS in the form of maps of regional potential distribution and maps of priority locations for vocational school development.Â Â